Interactive effects of casein micelle size and calcium and citrate content on rennet‐induced coagulation in bovine milk. Issue 6 (28th June 2019) - Priyashantha, Hasitha; Lundh, Åse; Höjer, Annika; Hetta, Mårten; Johansson, Monika; Langton, Maud
Abstract: Interactive effects of casein micelle size and milk calcium and citrate content on rennet‐induced coagulation were investigated. Milk samples containing small (SM) and large (LM) micelles, obtained from individual Holstein cows, were modified by addition of calcium and/or citrate and milk coagulation properties were evaluated in a full factorial design. The results showed that LM milk had a higher relative proportion of casein, coagulated faster, and resulted in a stronger gel than SM milk. Addition of calcium slightly decreased casein micelle size, while addition of citrate slightly increased micelle size. Calcium addition resulted in a shorter coagulation time and the strongest gels, while citrate addition increased the coagulation time and resulted in the weakest gels. Addition of calcium and citrate in combination resulted in intermediate coagulation properties. The interactive effect of micelle size and citrate was significant for gel strength. Microstructural differences between the milk gels were consistent with the rheological properties, for example, the micrographs revealed that a more homogeneous network was formed when calcium was added, resulting in a stronger gel. A more inhomogeneous network structure was formed when citrate was added, resulting in a weaker gel. Thus, variations in casein micelle size and in calcium and citrate content influence rennet‐induced coagulation in bovine milk. The calcium and citrate contents in Swedish milk have changed over time, whereby calcium content has increased and citrate content has decreased. In practical cheese making, calcium is added to cheese milk, most likely altering the role of inherent citrate and possibly influencing casein micelle size. The observed interaction effect between casein micelle size and citrate in this study, suggests that larger micelles with moderate citrate level will result in firmer gels, whereas a higher citrate content reduced gel strength more in case of large than SM. Since firmer gels are likely to retain more protein and fat than less firmer gels, this interaction effect could have implications in practical cheese production.